Developing the Instructional Video for Teaching Recount Text Writing through Guided Writing - Ummu Salamah; Happy Kusuma Wardani; Alimin; Abderrazak Zaafour; Souvik Das (Universitas Islam Negeri Palopo, 2026)
This research aimed to develop an instructional video for teaching recount text writing using the guided writing for tenth-grade students. This research employed a Research & Development (R&D) method using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The research was conducted at MA Manbaul Ihsan involving an English teacher and tenth-grade students. Data were collected through questionnaires, interviews, observation, and field notes. The developed video was validated by three experts to assess the product's feasibility. The results of the needs analysis indicated that students experienced difficulties with organizing ideas, developing sentences, and understanding the structure of a recount text. The students’ questionnaire showed that 85% of students highly needed learning media that combine video and technique. The validation results indicated that the developed video media was categorized as good and suitable for use in learning, although several aspects, such as visual design, language clarity, and presentation, still required improvement. The implementation results also showed positive responses from students, with most rating the video highly for visual appearance (87%), audio clarity (73%), and material suitability (73%). In addition, the video helped students understand the stages of writing a recount text and increased their engagement in the learning process. It can be concluded that the video learning media combined with the guided writing technique, was feasible to use as an alternative media in teaching writing recount texts. Additionally, this research result can serve as a starting point for further research to examine the effectiveness of the media in improving students’ writing ability, using a larger sample of participants.